Spatial impacts of digital industry development on carbon emission intensity: Empirical evidence from China - Li, Yaxuan; Lim, Jungmin (Journal of Climate Change Research, 2024)
The digital industry, as a new driver for high-quality economic development, is poised to play a pivotal role in energy conservation and carbon reduction in the era of climate change. This study explores the relationship between the digital industry's growth and carbon emission intensity, including empirical testing of this relationship. We also examine whether regional industrial and socio-economic factors in China induce spatial spillover effects on carbon emissions. To this end, we employ a Spatial Durbin Model (SDM) with fixed effects to analyze provincial-level panel data from 2005 to 2019. The empirical findings suggest that China's digital sector's progress can potentially lower carbon emission intensity. However, this reduction effect varies regionally, being more pronounced in the central and eastern regions than in the less developed western regions. When contemplated through a spatial lens, the digital industry's evolution appears to contribute to localized and broader carbon emission reductions. Yet, our study indicates that the spatial spillover effect among provinces remains limited. In addition, our research identifies a significant inverse relationship between economic development and carbon emission intensity, suggesting that economic growth may lead to reduced emissions. On the other hand, a larger labor force, aging population, foreign trade are positively correlated with higher emissions. Controlling for the level of digital industry development and industrial structure, R&D investment is found to be associated with higher emission intensity. This paper not only offers a novel understanding of the digital industry's impact on carbon emissions but also provides policy insights for integrating environmental sustainability into China's economic and social development towards carbon neutrality. KCI Citation Count: 0